Tertiary‐Alcohol‐Directed Functionalization of Remote C(sp3)−H Bonds by Sequential Hydrogen Atom and Heteroaryl Migrations. Issue 6 (12th January 2018) - Wu, Xinxin; Wang, Mingyang; Huan, Leitao; Wang, Dongping; Wang, Jinwei; Zhu, Chen
Abstract: Reported for the first time is a tertiary‐alcohol‐guided heteroarylation of remote C(sp 3 )−H bonds. The mild and direct generation of alkoxyl radicals from alcohols is enabled by visible‐light photocatalysis. A remote hydrogen atom and heteroaryl migration sequence are involved in the reaction. Many sensitive groups remain intact in the reaction, thus illustrating wide functional‐group compatibility. This protocol provides a practical strategy for the late‐stage modification of alkyl ketones. Abstract : Smart migration : A new method, the tertiary‐alcohol‐directed functionalization of remote C(sp 3 )−H bonds, is disclosed. The mild generation of the alkoxyl radical from the alcohol O−H bond under visible‐light photocatalysis is noteworthy and enables the hydrogen atom and heteroaryl group migration sequence. This method provides a practical strategy for the late‐stage modification of alkyl ketones. HAT=hydrogen‐atom transfer.